2009
DOI: 10.1080/09658210903012442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of instruction on learners’ ability to generate an effective pathway in the method of loci

Abstract: One of the most effective mnemonic techniques is the well-known method of loci. Learning and retention, especially of sequentially ordered information, is facilitated by this technique which involves mentally combining salient loci on a well-known path with the material to be learned. There are several variants of this technique that differ in the kind of path that is suggested to the user and it is implicitly assumed that these variants are comparable in effectiveness. The experiments reported in this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This may have occurred when list objects were not sufficiently distinct from other objects in the virtual world. The more distinct an object is (Massen, Vaterrodt‐Plünnecke, Krings, & Hilbig, ), the better the chance that it will be remembered and the smaller the risk of interference. Another possible reason for occurrence of such intrusions is that because there was no penalty for wrong answers, participants may have concluded that reporting any word could only enhance their result and used liberal response criteria.…”
Section: Discussionmentioning
confidence: 99%
“…This may have occurred when list objects were not sufficiently distinct from other objects in the virtual world. The more distinct an object is (Massen, Vaterrodt‐Plünnecke, Krings, & Hilbig, ), the better the chance that it will be remembered and the smaller the risk of interference. Another possible reason for occurrence of such intrusions is that because there was no penalty for wrong answers, participants may have concluded that reporting any word could only enhance their result and used liberal response criteria.…”
Section: Discussionmentioning
confidence: 99%
“…As Llewellyn's "lawsuit" example illustrates, a well-structured tableau containing very closely spaced locations may be effective; dream imagery may be much like this. Note, however, that such closely spaced MoL landmarks are less effective than are distantly spaced landmarks, such as one's route to work (Massen et al 2009). Nonetheless, this argument implies that dream locations may be irrelevant to dreaming's memory function; the essential ingredient may be the formation of composite dream images.…”
Section: Invention Of the Ancient Art Of Memory (Aaom) Is Attributed Tomentioning
confidence: 99%
“…1) after purportedly identifying the remains of comrades crushed in a temple collapse solely from his memory of where they were sitting before he fortuitously left the building. The MoL became common in Greek oral traditions and remains among the most effective mnemonic techniques (Massen et al 2009;Verhaeghen & Kliegl 2000). The MoL facilitates memory for both abstract and concrete material (Wang & Thomas 2000), is especially effective with serially ordered material (e.g., episodic memories) and is most effective when the imagined pathways used are self-generated versus other-generated (Bellezza & Reddy 1978).…”
Section: Invention Of the Ancient Art Of Memory (Aaom) Is Attributed Tomentioning
confidence: 99%
“…1) after purportedly identifying the remains of comrades crushed in a temple collapse solely from his memory of where they were sitting before he fortuitously left the building. The MoL became common in Greek oral traditions and remains among the most effective mnemonic techniques (Massen et al 2009; Verhaeghen & Kliegl 2000). The MoL facilitates memory for both abstract and concrete material (Wang & Thomas 2000), is especially effective with serially ordered material (e.g., episodic memories) and is most effective when the imagined pathways used are self-generated versus other-generated (Bellezza & Reddy 1978).…”
mentioning
confidence: 99%
“…As Llewellyn's “lawsuit” example illustrates, a well-structured tableau containing very closely spaced locations may be effective; dream imagery may be much like this. Note, however, that such closely spaced MoL landmarks are less effective than are distantly spaced landmarks, such as one's route to work (Massen et al 2009). Nonetheless, this argument implies that dream locations may be irrelevant to dreaming's memory function; the essential ingredient may be the formation of composite dream images.…”
mentioning
confidence: 99%